GUIDELINE FOR DEVELOPING THE POTENTIAL OF OPERATIONS STAFF TO USE POINT OF SALE TECHNOLOGY IN SMALL AND MEDIUM-SIZED RESTAURANT BUSINESSES (SMES) IN BANGKOK - Srichomngam, Rakchanok; Smith, Natnaree (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This qualitative research aimed (1) to explore the readiness and feasibility of small and medium-sized restaurant businesses (SMEs) in Bangkok regarding technology adoption and operational practices in real-world settings, (2) to examine the current business environment in the restaurant industry, (3) to analyze the potential of operational staff in restaurant businesses, and (4) to establish guidelines for developing the potential of operational staff in terms of using Point of Sale (POS) technology. Data were collected through non-participant observation, in-depth interviews, and focus group discussions with 21 key informants, including representatives from government agencies, the private sector (entrepreneurs), and staff from Southern Thai restaurants in Bangkok. Data were analyzed using content analysis and presented in descriptive format. The findings revealed several issues. First, most restaurants were ready in terms of service quality and technology implementation for management. Second, the restaurant business environment faces intense competition, economic slowdown, and declining consumer purchasing power, while operational costs are increasing. Third, entrepreneurs should prioritize developing operational staff capabilities in terms of using POS technology and selecting appropriate technology to enhance accuracy and service efficiency. Finally, the guidelines for developing the potential of operational staff should reflect each business's strengths and objectives, along with four operational factors, comprising human resources (emphasizing training and organizational culture building), management (establishing systematic work processes), technology (selecting appropriate technology), and finance (managing budgets efficiently) to enhance competitiveness and sustainable growth.